After 6 years both the trees will be of same height
Solution:
Let "x" be the number of years that both the trees take to be the same height
Type A is 4 feet tall and grows at a rate of 22 inches per year
We know that,
1 feet = 12 inches
4 feet = 4 x 12 inches = 48 inches
Therefore height of type A after x years is given as:
⇒ initial height + 22 inches per year
⇒ 48 + 22(x)
⇒ 48 + 22x ---- eqn 1
Type B is 6 feet tall and grows at a rate of 18 inches per year
We know that,
1 feet = 12 inches
6 feet = 12 x 6 inches = 72 inches
Therefore height of type B after x years is given as:
⇒ initial height + 18 inches per year
⇒ 72 + 18(x)
⇒ 72 + 18x ---- eqn 2
For height Type A to equal height Type B:
Height Type A = Height Type B
eqn 1 = eqn 2
48 + 22x = 72 + 18x
22x - 18x = 72 - 48
4x = 24
x = 6
Therefore after 6 years both the trees will be of same height